Implementation of Mechanical Processing Machines in Traditional Medicines (Jamu) Production - Isti Purwaningsih; Usman Effendi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACT The objective of this activity is to implement the washing machine for rhizome and hydraulic press machine to improve the performance and efficiency of jamu production process. There are several activities such as: (1) surveying at small medium entrerprises of traditional medicine in Batu, “Ragil” and “Bu Roes” and doing preliminary evaluation, (2) designing and assembling washing machine and hydraulic press machine, (3) training, (4) implementing machine in SMEs partner, then (5) monitoring and evaluation. The result of this activity showed that washing machine performance had average input capacity of 5 kg/process/5 minutes with 95% efficiency. Hydraulic press had average input capacity of 10 kg/process/ 5 minutes. The benefits of both machines implementation were time and power saving, and increasing production hygiene and efficiency. Keywords: Traditional medicine, washing machine, hydraulic press machine